(untitled) (Global Journal of Human-Social Science, 2022)
Scrum is one of the agile methodologies that companies seek to use for project management Based on this fact a mobile educational game was developed to help the teacher and dynamize the class having some steps to follow containing two steps in the first one the student will complete the quiz to know his statistics of errors and successes of the chosen answers in the quiz about the Scrum method In the final step the construction of a city must be carried out that the student must fulfill within this construction he will learn about roles events and artifacts linked to Scrum through rules and in the continuation of the game